THE INFLUENCE OF PRICE, PROMOTION, AND PRODUCT QUALITY ON STUDENTS' PURCHASE DECISIONS ON SMARTFREN DATA PACKAGES PRIMA UNIVERSITY OF INDONESIA - Romi Riszky Hidayat Sitepu; Januardin Januardin (Jurnal Ekonomi, 2022)
The purpose of this study was to determine the effect of price, promotion, and product quality on the decision to purchase Smartfren data packages for Prima Indonesia University students. In processing this research data using SPSS 25. The population of this study consisted of 285 students at the University of Prima Indonesia. In this study, a quantitative methodology was used and the method for determining probability sampling was purposive sampling. The test results reveal that partially the price, promotion, and product quality variables have a positive and significant influence on the decision to purchase Smartfren data packages for Prima Indonesia University students. Simultaneous test results show that purchasing decisions are influenced in the same way by price, promotion, and product quality at the same time.